Prevalence of Chronic Toxoplasma gondii Infection Among Women Who Had Undergone Abortion in Tobruk and Surrounding Areas, Libya. - Boshra Abdalnaser; Najwa Bellhamad; Abdulsalam Saleh; Randa Mahmoud; Mohammd Abd Alati; Fathi Hamd (AlQalam Journal of Medical and Applied Sciences, 2025)
Toxoplasmosis is a major cause of infection among pregnant women exposed to cat feces or consuming contaminated, undercooked meat. In this study, 80 serum samples were collected from women who had miscarried in Tobruk, eastern Libya. All samples were transported to a specialized center in Tobruk for testing for Toxoplasma gondii (IgA) antibodies using the enzyme-linked immunosorbent assay (ELISA), an important biotechnology for detecting this parasite, following the supplier’s instructions. After testing the samples from the miscarried women, Toxoplasma gondii antibodies were found in 54% of the samples. This percentage indicates a high prevalence of this parasite. According to this study, further surveys should be conducted in other areas of Libya to provide statistical data on the prevalence and impact of this parasite, as it is a real risk factor for miscarriage, in addition to the recent rise in household cats.